2019
DOI: 10.1590/1982-0194201900069
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa da taxa de filtração glomerular em pessoas vivendo com HIV

Abstract: Resumo Objetivo Avaliar os fatores associados à estimativa da Taxa de Filtração Glomerular (eTFG) em pessoas vivendo com HIV. Métodos Estudo transversal e analítico, com avaliação de 340 pessoas em atendimento ambulatorial no município de Ribeirão Preto-SP. Calculou-se a eTFG através da fórmula Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). Foi realizado análise univariada com os testes Qui-quadrado e Exato de Fisher, com p<0,05. Resultados Identificou que 114 (34,1%) dos participantes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The prevalence of CKD associated with HIV varies geographically, by population and by period of the year ( 13 , 16 - 17 ) , due to genetic heterogeneity, to the initiation of the ART ( 18 ) and to the different definition methods for CKD in each region, varying between 2% and 38% ( 13 , 19 ) . A study carried out in the Southeast region of Brazil showed that 35% of PLHIV using nephrotoxic ARDs for at least 6 months showed changes in the renal function ( 20 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of CKD associated with HIV varies geographically, by population and by period of the year ( 13 , 16 - 17 ) , due to genetic heterogeneity, to the initiation of the ART ( 18 ) and to the different definition methods for CKD in each region, varying between 2% and 38% ( 13 , 19 ) . A study carried out in the Southeast region of Brazil showed that 35% of PLHIV using nephrotoxic ARDs for at least 6 months showed changes in the renal function ( 20 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relevance of the matter ( 11 - 12 ) and to the scarcity of research studies on this topic at the national level ( 20 ) , it is necessary to deepen studies on it and to expand the vision of comprehensive care for PLHIV, with the aim of preventing diseases, promoting health and timely treatment ( 20 ) . In view of the above, the objective of this study is to analyze the factors associated with CKD in PLHIV.…”
Section: Introductionmentioning
confidence: 99%